Renal Radionuclide Imaging, an Evergreen Forty Years Old - De Palma, D.; Santos, A. I. (Klinische Pädiatrie, 2014)
Urinary tract congenital abnormalities (UCA) and febrile infections (UTI) are, respectively, 2 of the commonest congenital and acquired health problems in childhood. In both, radionuclide imaging still represent a cornerstone of diagnostic imaging, although the involved techniques are more or less the same from the early ’80 s. During the last 2 decades, published papers focused on a deep revision about the optimal use and usefulness of such imaging tools in affected children, with the aim of reducing invasiveness, radiation burden and costs without losing efficacy. This approach leads to different results. In UCA, no consensus for a diagnostic algorithm was up to now reached, whilst, about febrile UTIs, guidelines were published in 2007 by the UK’s National Institute for Clinical Excellence (NICE) and by the European Society of Paediatric Radiology (ESPR), in 2011 by the American Academy of Paediatrics (AAP), and in 2012 by the Italian Society of Paediatric Nephrology (SINP). Nevertheless, new data continuously arise and the scientific debate always revives. Every imaging tool now available has its own strengths and weaknesses, and so all published guidelines. All this body of knowledge must be critically analysed for obtaining a complete, up-to-date and flexible overview about these “always hot” topics.
Keywords: congenital uropathies; urinary tract infection; vesicoureteral reflux; dynamic renal scintigraphy; static renal scintigraphy; cystography